Analisis PeramalanProduksi Panen Pisang Cavendish Menggunakan Exponential Smoothingke Product Sunpride dan Bali Fresh di PT. Nusantara Segar Abadi Bali - I Nyoman Galih Oki Putra; I Gusti Ngurah Apriadi; Ida Bagus Putu Gunadnya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
PT. Nusantara Segar Abadi Bali was established in 2019. PT. NSA BALI has 2 products produced from cavendish bananas, namely Cavendish Sunpride Banana and Cavendish Bali Fresh Banana. Supply from the harvest is expected to meet the monthly production target of PT. NSA BALI. This r esearch is conducted to get the right forecas ting method to meet the needs of production. In this study using two modeling methods, namely Single Exponential Smoothing and Triple Exponential Smoothing methods. For this study, the data used is secondary data, namely data from January 2019 to Juli 2023 . In this study using model validation, namely MAD, MSE and MAPE. It is known that this study obtained forecasting validation results, namely MAD 17%, MSE 58% MAPE 24% in the Single Exponential Smoothing method, while the Triple Exponential Smoothing metho d obtained the number of forecasting validations, namely MAD 43%, MSE 11% MAPE 54%. In the Single Exponential Smoothing method, the number of forecasts can meet the production target in November 2022 to Juli 2023, while in the Triple Exponential Smoothing method the time that can meet the number of production targets is in September 2022 to Juli 2023